PENERAPAN LOGIKA FUZZY DALAM PENGUKURAN TINGKAT KENYAMANAN TERMAL SUATU RUANGAN BERDASARKAN SISTEM VENTILASI - Andriani, Santy; Simanjorang, R. Magdalena; Sulindawaty, Sulindawaty; Hasugian, Penda Sudarto (STMIK Kaputama, 2019)
Thermal is a very important thing in influencing the level of comfort of a room. The important factor for the thermal comfort of a room is influenced by several factors, namely the height of the building which also affects the wind speed that enters the room, air temperature in the room, relative humidity level, the activity of the occupants That can affect the speed of metabolism and clothing imposed by the occupants of the room. PMV (Predicted Mean Vote) which has a range of-3 to 3 which represents the cold codition until heat, can be determined the value of its condition by using the fuzzy logic. The fuzzy logic can decide on which conditions the room is taking into account the weight of its membership.